Trend Analysis on the Automation of the Notebook PC Production Process - Yeh, Chin-Ching (International journal of automation and smart technology, 2025)
Notebook PCs are among the Taiwanese electronic products that generate the highest production value and market share. According to the ITRI IEK statistics, the domestic Notebook PC - production value in 2011 was about NT $2.3 trillion. Of about 200 million notebook PCs in global markets in 2011, Taiwan’s notebook PC output accounts for more than 90% of them, meaning that nine out of every ten notebook PCs in the world are manufactured by Taiwanese companies. For such a large industry with its output value and quantity, the degree of automation in production processes is not high. This means that there is still a great room for the automation of the notebook PC production process, or that the degree of automation of the production process of the laptops cannot be enhanced. This paper presents an analysis of the situation.